"Litigation Is Our Last Resort": Addressing Uncertainty, Undone Science, and Bias in Court to Assert Indigenous Rights. Issue 2 (1st June 2020) - Panikkar, Bindu
Abstract: The permitting of large-scale industrial mines is often controversial and litigious. This article examines three legal battles over the exploratory permitting of the Pebble mine in southwestern Alaska to examine the logics and rationalities used to legitimize the permitting, the alternate epistemic arguments made by the resistance movements to redraw state-constructed boundaries, and differing definitions of land-based resources, pollution, and bias. It asks how conflicting knowledge claims and epistemic injustice are debated and settled in court. All three legal cases observed demonstrate conditions of scientific uncertainty, undone science, and bias, failing to hold space for diverse representations within legal claims. Citizen science is partially successful in addressing epistemic injustice, but to effectively mediate justice, law must distinctively question both knowledge construction and phronetic risks, including values, intent, bias, privilege, and agency, and take into consideration the ontological multiplicities and civic epistemologies of the parties within legal claims.